2023
DOI: 10.3390/jpm13010135
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Spliced Isoforms of MUC4 and ADAM12 as Biomarkers for Colorectal Cancer Metastasis

Abstract: There is a pertinent need to develop prognostic biomarkers for practicing predictive, preventive and personalized medicine (PPPM) in colorectal cancer metastasis. The analysis of isoform expression data governed by alternative splicing provides a high-resolution picture of mRNAs in a defined condition. This information would not be available by studying gene expression changes alone. Hence, we utilized our prior data from an exon microarray and found ADAM12 and MUC4 to be strong biomarker candidates based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(52 reference statements)
2
0
0
Order By: Relevance
“…In this study, through comprehensive analyses by TSNAD v2.0 NetMHCpan v4.0, 157 INDELs, 1 TS, and 57 SNVs were identified as potential neoantigens for MUC mutated genes showing high affinity with MHC-I. Interestingly, 94 INDELs were for MUC4, which is consistent with a previous study that found that MUC4 was highly alternative splicing in CRC [ 68 ].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, through comprehensive analyses by TSNAD v2.0 NetMHCpan v4.0, 157 INDELs, 1 TS, and 57 SNVs were identified as potential neoantigens for MUC mutated genes showing high affinity with MHC-I. Interestingly, 94 INDELs were for MUC4, which is consistent with a previous study that found that MUC4 was highly alternative splicing in CRC [ 68 ].…”
Section: Discussionsupporting
confidence: 88%
“…Based on analyses with TSNAD v1.0 NetMHCpan v4.0 [26,60,61] MUC4, which is consistent with a previous study that found that MUC4 was highly alternative splicing in CRC [63].…”
Section: Cd4+ T Cells Activated B Cells T Neutrophil Cells Dendritic ...supporting
confidence: 90%
“…Current methods for diagnosing and monitoring OPSCC remain insufficient; the development of biomarkers can help in early patient diagnosis and monitoring of treatment response, thereby improving the survival rates and lowering the recurrence rates. The development of predictive biomarkers can predict a disease's course and ascertain therapeutics' success [19]. Differential expression analysis scrutinizes gene expression motifs and collocates the molecular processes underlying convoluted illnesses.…”
Section: Introductionmentioning
confidence: 99%